GIS-material for the archaeological project: Burial ground, skeleton and agricultural layers by the penal institution in Skänninge - Archaeology department, Östergötland County Museum (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Before the rebuildning of the National Road 32/50, a field evaluation of the ancient monuments RAÄ 37 and 38 in the city of Skänninge, was carried out. During the survey, nine graves, of which seven unmarked childrens' graves and two stone settings, were found. South of the burial ground, two overlapping agricultural layers and a few ard marks were found. In this area was also found an inhumation grave, part of a stream bed/ditch and a road. In the inhumation grave remains of wood were found, interpreted as a coffin. The individual was osteologically determined as a male.The skeleton bore traces of severe violence. The grave has been dated to the Viking Age.

One of the most remarkable results of the evaluation was the high level of lost and damaged archaeological remains and ancient monuments due to ploughing, during the decade that has passed between the initial archaeological assessment and the field evaluation. It is thus of the highest importance to excavate the archaeological remnants before they are lost by ploughing, both within and outside of the immediate road area.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the field evaluation was to establish and describe the character, dating, expansion, composition and complexity of the archaeological remains in question (burial grounds and abandoned fields). The purpose was also to investigate whether the were other archaeological remnants, such as settlement remains, within the investigation area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför ombyggnaden av Rv 32 till Rv 50 har en arkeologisk förundersökning utförts av RAÄ 37 och 38, Skänninge stad. Vid undersökningen framkom nio gravar, varav sju omarkerade brandgravar och två stensättningar. Söder om gravfältet noterades två ovanpå varandra liggande odlingslager liksom även ett mindre antal årderspår. I detta område påträffades också en skelettgrav, delar av en bäckfåra/dike och en väg. I skelettgraven påträffades trärester som tolkats som en kista. Osteologiskt bestämdes individen ha varit en man. Skelettet visade spår att kroppen utsatts för kraftigt våld. Graven har daterats till vikingatid.

Ett av undersökningens mest påfallande resultat var den höga graden av bortodling som skett under det decennium som passerat mellan utredningen och förundersökningen. Sammantaget medför detta att det är av största vikt att undersöka de fornlämningar som ligger inom vägområdet, men även de som kommer att kvarligga utanför den nya vägsträckningen. I annat fall kommer de sannolikt att ha plöjts bort inom en snar framtid.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att fastställa och beskriva de aktuella fornlämningarnas (gravfält och odlingsytor) karaktär, datering, utbredning, omfattning, sammansättning och komplexitet. En fråga gällde även om det fanns andra typer av lämningar såsom boplatslämningar inom förundersökningsområdet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Gravfält, skelett och odlingslager vid Kriminalvårdsanstalten i Skänninge
Keywords: Late Iron Age; yngre järnålder; Middle Ages; medeltid; Early Iron Age; äldre järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive